Dermatofibrosarcoma protuberans misdiagnosed as keloid and treated with triamcinolone acetonide - Erick Horta Portugal; José Carlos Ribeiro Resende Alves; Rebeca Paohwa Liu da Fonseca; José de Souza Andrade Filho; Augusto César de Melo Almeida; Izabella Costa Araújo; Nárlei Amarante Pereira; Raíssa Lemos Ferreira da Silva (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: Dermatofibrosarcoma protuberans is a rare skin tumor with intermediate malignancy, low metastatic potential, and high recurrence rates after surgical treatment. Owing to a possible clinical resemblance with hypertrophic scars and keloids, the correct diagnosis is fundamental for treatment success. The objective of the present work is to report on four cases of dermatofibrosarcoma protuberans misdiagnosed as keloid and treated elsewhere with infiltration of triamcinolone acetonide. METHOD: Between November 1983 and January 2008, four patients with dermatofibrosarcoma protuberans who had undergone intralesional infiltration with triamcinolone acetonide elsewhere were treated because of an erroneous diagnosis of keloid. Radical surgical excision was performed, and 3 cm of healthy tissue was removed from the side margins, including the deep margin, an anatomical structure not infiltrated by the tumor. The patients underwent long-term periodic medical evaluations. RESULTS: The patients were followed-up for an average of 159 months. Three patients (75%) are still alive without signs of disease at the time of this report. One patient (25%) died of the disease after an attempt to remove the advanced recurrent tumor using extensive craniofacial surgery. Recurrence occurred 7 years after the radical operation. CONCLUSION: Dermatofibrosarcoma protuberans must be considered in the differential diagnosis of keloids. Intralesional infiltration with triamcinolone acetonide should only be performed after diagnostic confirmation , which may require pathological examination. A careful clinical examination and knowledge of the lesion favor a precise diagnosis and an appropriate treatment.